PECULIARITIES OF GRANTING LEAVE TO EMPLOYEES UNDER MARTIAL LAW - Копчикова, І.В.; Китайчук, Т.Г.; Покиньчереда, В.В. (SWorldJournal, 2024)
The article highlights key changes in the organization of labor relations during martial law in Ukraine. It was noted about the multi-level regulatory regulation of labor remuneration. Changes in the current legislation and new instruments related to the